General Knowledge and Misconceptions about HIV/AIDS among the University Students in Malaysia - M. H. M., Nazmul; Y., Farzana; S., Deepthi; M. K. K., Fazlul; A., Najnin; C., Srikumar (Diva Enterprises PVT. LTD., 2018)
This study was aimed to determine the general knowledge and misconceptions among the undergraduate students in a private university in Malaysia. Data was collected from a stratified random sample of 180 students using a validated questionnaire survey to assess the general knowledge and misconceptions about HIV/AIDS. The data was analysed by using the SPSS software and Chi-square test was used to find the p-value for each of the questions. The average mean score assessing the general knowledge of the students in was 82.32%, where the Health Science students scored 45.11% with a standard deviation of 0.017 and the Non-Health Science students scored 36.15% with a standard deviation of 0.026. When comparing each question using the Chi-square test, most of the answers of the Health Science students and Non-Health Science students showed a significant difference where the p-value was <0.05. From the results of this study it is clear that the Health Science students had better knowledge and fewer misconceptions than the Non-Health Science students.